Strengthening Employee Performance Through Sustainable HRM: Examining the Moderating Role of Individual Culture (Architecture Image Studies, 2026)
This study aims to analyse the influence of employee engagement, employee communication, attitude, transformational leadership, and Neuro-Linguistic Programming (NLP) Learning on employee performance and its implications for Sustainable Human Resource Management, with employee culture as a moderating variable. This study uses a quantitative approach with a survey method. The research population consists of managerial-level employees (leaders to managers) at companies in West Java who participated in the ‘X’ Job Training Institute (LPK) training programme, with a total of 360 respondents. The sampling technique used was purposive sampling. Data were collected through structured questionnaires and analysed using Structural Equation Modelling Partial Least Squares (SEM-PLS). The results showed that employee engagement, employee communication, transformational leadership, and NLP learning had a positive and significant effect on employee performance, while attitude had no significant effect. Furthermore, employee performance, employee engagement, attitude, transformational leadership, and NLP learning have a positive and significant effect on sustainable HRM, while employee communication does not have a significant effect. Additionally, employee culture acts as a moderating variable in the effect of employee engagement, employee communication, and transformational leadership on employee performance, as well as attitude and transformational. This study contributes theoretically by integrating individual factors, organizational factors, and NLP Learning into a comprehensive Sustainable HRM framework. Practically, the findings provide valuable insights for organizations and training institutions in designing more effective and Sustainable human resource development strategies.